A biosonar model of finless porpoise (Neophocaena phocaenoides) for material composition discrimination of cylinders - Feng, W.; Zhang, Y.; Wei, Chong (Acoustical Society of America, 2019)
Research into the physical mechanism of odontocetes biosonar has made great progress in the past several decades, especially on wave propagation and biosonar beam formation in the foreheads of odontocetes. Although a number of experimental studies have been performed, the physical mechanism of odontocetes underwater target discrimination has not yet been fully understood. Previous research has experimentally studied the finless porpoise’s target discrimination using cylinders different in material [Nakahara, Takemura, Koido, and Hiruda (1997). Mar. Mamm. Sci. 13(4), 639–649]. The authors proposed a computed tomography based finite element biosonar model to simulate the detailed process of a finless porpoise click emission and target detection in order to gain a further understanding of the underlying physical mechanism. The numerical solutions of resonance features of both steel and acrylic cylinders in this study are very consistent with the analytic solutions. Furthermore, the simulated outgoing clicks and echoes match the experiment results measured by Nakahara et al. The beam patterns of the scattered field were extracted and the resonance features of cylinders in different materials were analyzed. This method in this study could be used to study some other odontocetes that are inaccessible for experimental work and could also provide physical information for intelligent biomimetic underwater signal processors design.